Trends in rainfall and hydrometeorological disasters in new capital city of Indonesia from long-term satellite-based precipitation products - Ramadhan, Ravidho; Marzuki, Marzuki; Suryanto, Wiwit; Sholihun, Sholihun; Yusnaini, Helmi; Muharsyah, Robi; Hanif, Muhammad (Remote Sensing Applications: Society and Environment, 2022)
The Indonesian government has decided to move its capital city from Jakarta in Java to Nusantara Capital City (IKN) on Borneo island. This study investigates the trend and variability of rainfall in the IKN and two buffer cities and its relation to hydrometeorological disasters. We analyze 20 years of Integrated Multi-Satellite Retrievals for GPM (IMERG) version 6 data and hydrometeorological disaster information from the National Agency for Disaster Countermeasure. The annual rainfall, the extreme rain index of R95p (number of very wet days), and R99p (number of very extremely wet days) show a slightly decreasing trend. However, the index of consecutive wet days (CWD) increases, resembling the rising number of floods and landslides. Rainfall shows robust seasonal and diurnal variations. Peak rainfall occurs in November-December and March-April, while the driest period is observed during August-October. Dry months associated with El-Nino, can cause severe dry conditions and increase the potential for catastrophic forest fires. The peak precipitation amount and frequency were observed in the early morning and the second peak in the afternoon. Mainland areas tend to have a peak occurring later than those on the coast and ocean. The results of this study can be additional information in formulating a strategic plan to anticipate future hydrometeorological disasters in IKN.